Growing Information System: New Vision in Integration of Information System into Organization - Husni Sastramihardja; Sukrisno Mardiyanto; Iping Supriana; Iman Sudirman; D. A. Wassenaar (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
Since organization change from stable to emergent condition, information system (IS) as part oforganization should have capability to follow the changes of requirement from the functional purposes andinteractivities with the users. Need of new strategy in IS development methodology is urgent. Integration of ISand organization could be seen as new vision and growing IS could be the new paradigm in IS developmentmethodology. The research conducted concludes that growing IS could be developed using role and task asorganic constructor. This paper presents theoretical approach leads to requirement of growing IS model (GiSM).Key words: growing information system, emergent condition, organic constructor, role, task